Real Performance of Pedagogic Competencies of Teacher Learning in The Classroom in Elementary Schools - Paramudita, Alfiyan; Fakhruddin, Fakhruddin; Supraptono, Eko (Educational Management, 2021)
This study aims to determine the pedagogical competence of teachers in learning process inside the classroom. This study uses a qualitative approach with descriptive research methods. Data collection was carried out by observation, interviews, documentation data reduction, display data, and conclusion drawing / verification . The research subjects were the headmaster and teachers at SDN Pati Kidul 01. Based on the results of the study, the result of this study indicate that the real performance of teacher pedagogical competence is reflected as follow, (1) utilization of technology by the teacher as an alternative in the learning process in the classroom by looking at the conditions of the school, the condition of students, the environment, and infrastructure. (2) the teacher connects the material to be taught with new news and then draws it into the conclusions so that students be able to understand the values within each subject. (3) three aspects in the assessment are knowledge, attitudes, and skills.